2019
DOI: 10.1097/sla.0000000000002810
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Short-term and Oncologic Outcomes of Minimally Invasive Versus Open Pancreaticoduodenectomy Across Low and High Volume Centers

Abstract: Patients selected to receive MIPD for cancer have equivalent short-term and oncologic outcomes, when compared with patients who undergo OPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 22 publications
4
102
0
Order By: Relevance
“…Despite initial hesitance, MIPD has been increasingly adopted over the past decade. A recent review of the National Cancer Database in the United States reported that between 2010 and 2015, 3754 (17.1%) of 22 013 PDs for pancreatic cancer were performed via MIS . Furthermore, there was no difference in perioperative and oncological outcomes between MIPD and open PD (OPD) in this database registry study.…”
Section: Discussionmentioning
confidence: 63%
“…Despite initial hesitance, MIPD has been increasingly adopted over the past decade. A recent review of the National Cancer Database in the United States reported that between 2010 and 2015, 3754 (17.1%) of 22 013 PDs for pancreatic cancer were performed via MIS . Furthermore, there was no difference in perioperative and oncological outcomes between MIPD and open PD (OPD) in this database registry study.…”
Section: Discussionmentioning
confidence: 63%
“…There are two ongoing RCTs comparing EA with intravenous morphine 43 and with intravenous hydromorphone 44 , designed to determine how analgesic technique influences the incidence of complications and mortality after pancreatoduodenectomy. It will be interesting to see how the increasing use of minimally invasive surgery will influence indications for analgesic techniques 45 . Recent experience 46 -48 with sublingual sufentanil (non-invasive, rapid absorption, rapid pain relief, few side-effects) seems promising, leading to a proposed RCT comparing EA with sublingual sufentanil in patients undergoing pancreatoduodenectomy (www .trialregister.nl; TC 7318).…”
Section: Discussionmentioning
confidence: 99%
“…The development of MIPD was based on Gagner and Pomp's original LPD description from 1994 [22]. Several studies from high-volume centers have reported that MIPD might be feasible and confer advantages over OPD for benign lesions and periampullary malignancy [23][24][25]. However, reservations concerning the safety of MIPD persist as the majority of hospitals performing MIPD were low-volume centers, and its use has been associated with increased morbidity and mortality [26][27][28].…”
Section: Discussionmentioning
confidence: 99%